Effects of subclinical hypothyroidism during pregnancy on mtDNA methylation in the brain of rat offspring - Liangzhuo Xie; Yangling Huang; Xiande Ma; Xiaoqiu Ma; Jian Wang; Tianshu Gao; Wei Chen (BMC Neuroscience)
Abstract Objective This study aims to investigate the impact of subclinical hypothyroidism (SCH) during pregnancy on mitochondrial DNA (mtDNA) methylation in the brain tissues of rat offspring. Materials and methods Sixteen SD rats were randomly divided into two groups: control group (CON) and SCH group. BS-seq sequencing was used to analyze mtDNA methylation levels in the offspring’s brain tissues; the 2,7-dichlorofluorescin diacetate (DCFH-DA) probe method was employed to detect reactive oxygen species (ROS) levels in brain tissues; electron microscopy was utilized to observe the mitochondrial structure in the hippocampal tissues of the offspring. Results In the analysis of differentially methylated regions (DMRs), the mitochondrial chromosome in the SCH group exhibited 23 DMRs compared to the control group. ROS levels in the brain tissues of the SCH group were significantly higher than those in the control group (P < 0.05). The mitochondrial structure in the hippocampus of the SCH group was less intact compared to the CON group. Conclusion Subclinical hypothyroidism in pregnant rats may alter the mtDNA methylation pattern in the brains of their offspring, potentially affecting mitochondrial function and structure.